Let it not be that nursing that asks for silence: participation in social movements and sociopolitical-emancipatory knowledge - Ana Renata Moura Rabelo; Kênia Lara da Silva (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the expression of sociopolitical-emancipatory knowledge, based on the participation of women-nurses in social movements, and the implications for nursing care. Methods: a research-interference, whose data were obtained from narrative interviews with six women-nurses inserted in social movements and with political representation. Data were submitted to discourse analysis, based on Michel Foucault. Results: women-nurses' social and political involvement is driven by the contexts of life and work, marked by gender inequalities. Ability to criticize oneself, the profession and health policies and practices are presented as expressions of sociopolitical-emancipatory knowledge. Nursing care is conceived as a political practice that, influenced by learning from social movements, must go through a denial of the historically performed form. Final Considerations: participation in social movements triggers sociopolitical-emancipatory knowledge, resulting in differentiated care, a way of acting oriented towards reducing inequalities.